Academic Supervision in Improving the Quality of School Culture - Utaminingtyas, Endah; Hanafi, M Syadeli; Suherman, Suherman (PPSDP International Journal of Education, 2023)
This study aims to describe the implementation of academic supervision in the context of school quality culture. The approach used in this research is quantitative with a descriptive research design. The population and sample of the study were all teachers of Nurul Fikri Serang Islamic Middle School and High School. The analysis technique used is descriptive percentage. Academic supervision activities aim to improve the teacher’s learning process in the classroom. The supervisory activity is carried out by a team of supervisors under the coordination of the school principal. Supervisors have requirements that meet competence according to applicable regulations. The results of collegial-based academic supervision illustrate that aspects of learning in general have very good grades, so they really help teachers in improving the quality of the learning process in class. Collegial-based academic supervision creates a culture of school quality, namely cooperation, democracy, constructiveness, humanism so that overall supervision activities build a culture that is sustainable, especially the quality of learning.